Marijuana Federalism : Uncle Sam and Mary Jane - Adler, Jonathan H. (Book collections on Project MUSE., 2020)
More than one-half of the 50 states have legalized the use of marijuana at least for medical purposes, and about a dozen of those states have gone further, legalizing it for recreational use. Either step would have been almost inconceivable just a couple decades ago. But marijuana remains an illegal-controlled substance under a 1970 federal law, so those who sell or grow it could still face federal prosecution. How can state and federal laws be in such conflict? And could federal law put the new state laws in jeopardy at some point? This book, an edited volume with contributions by legal scholars and policy analysts, offers a detailed examination of these and other questions surrounding a highly unusual conflict between state and federal policies and laws. This book surveys the constitutional issues that come into play with this conflict, as well as the policy questions related to law enforcement at the federal versus state levels. It also describes specific areas - such as banking regulations - in which federal law has particularly far-reaching effects. Readers will gain a greater understanding of federalism in general, including how the division of authority between the federal and state governments operates in the context of policy and legal disputes between the two levels. This book also will help inform debates as other states consider whether to jump on the bandwagon of marijuana legalization. --